2018
DOI: 10.1016/j.microrel.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

A new hermetic sealing method for ceramic package using nanosilver sintering technology

Abstract: High reliable packaging materials are needed for electronics when they work at harsh environments. Among which, the nanosilver material has been widely studied and applied in power electronics due to its low processing temperature and high reliability. This paper investigates the bonding properties of nanosilver sintered hermetic cavity. There are two kinds of lids used in this study, including copper lid and silicon lid. The X-Ray and C-Mode Scanning Acoustic Microscopy (C-SAM) results revealed that delaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…An organic sealed package will be ultimately intruded by water vapor or gases due to the permeability of organic materials [1]. Active devices in harsh environments are preferentially recommended in a metal or ceramic hermetic package [2][3][4]. Sealing a package with a lid, usually the final process in packaging, allows an integrated circuit assembled inside in an isolated environment to prevent aggression of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…An organic sealed package will be ultimately intruded by water vapor or gases due to the permeability of organic materials [1]. Active devices in harsh environments are preferentially recommended in a metal or ceramic hermetic package [2][3][4]. Sealing a package with a lid, usually the final process in packaging, allows an integrated circuit assembled inside in an isolated environment to prevent aggression of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that thermal cycling, high-temperature storage, high-humidity storage, and a pressure cooker test failed to induce failure. Zhang et al [ 3 ] investigated the bonding strength of a nanosilver sintered hermetic cavity with copper and silicon lids. Their results showed that the copper lid suffered delamination in the bonding layer, whereas the silicon lid exhibited great bonding quality.…”
Section: Introductionmentioning
confidence: 99%
“…Farisi et al [4] developed a low-temperature wafer-level hermetic packaging technology based on thermal compression bonding. Their analyses revealed that the bonding shear strength of the newly proposed technology exceeded 100 MPa and its leak rate was below 1.67 × 10 −15 Pa•m 3 •s −1 . Huang et al [5] also developed low-cost and low-temperature hermetic technology based on a eutectic PbSn solder and Cr/Ni/Cu bonding pad.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the development of packaging solders for the third generation of semiconductors, and the development of new leadfree interconnection technologies are getting more and more attention (Cheng et al, 2013). New lead-free interconnect technologies include sintering of Ag powder (Zhang et al, 2018(Zhang et al, , 2019Liu et al, 2018) and low-temperature diffusion of precious metals (Yoon and Lee, 2018;Wei et al, 2018;Peng et al, 2018). These processes can obtain good connection and be environmental friendly, but the process is complicated and the cost is high.…”
Section: Introductionmentioning
confidence: 99%